Early assessment of aspiration risk in acute stroke by fiberoptic endoscopy in critically ill patients - Mohamed Saad Abdelaziz Elsyaad; Akram Muhammad Fayed; Mohamed Mostafa Abdel Salam Megahed; Nesrine Hazem Hamouda; Ahmed Moustafa Elmenshawy (Acute and Critical Care, 2022)
Background Fiberoptic endoscopic evaluation of swallowing (FEES) has been recommended to assess aspiration in stroke. This study aimed to determine the diagnostic and prognostic roles of FEES in the early assessment of aspiration, intensive care unit (ICU) stay and mortality in acute stroke patients. Methods Fifty-two patients with acute stroke admitted to the Alexandria Main University Hospital were included. Complete examinations and assessment of aspiration using the 8-point penetration-aspiration scale (PAS) with FEES protocol were performed. Results The patients were classified into three groups: normal with no or low risk of aspiration (n=15, 27.3%; PAS level 1), low to moderate risk (n=8, 14.5%; PAS level 2–4), and high risk (n=32, 58.2%; PAS ≥5). There was high incidence of aspiration pneumonia, prolonged ICU stay, and mortality in both moderate- and high-risk groups (P=0.001, P<0.001, and P<0.001, respectively). The PAS score predicted aspiration pneumonia (hospital-acquired pneumonia) with sensitivity and specificity of 80.0% and 76.0%, respectively (negative predictive value [NPV], 76.0; positive predictive value [PPV], 80.0; 95% confidence interval [CI], 0.706–0.940) and mortality with sensitivity and specificity of 88.46% and 68.97% (NPV, 87.0; PPV, 71.9; 95% CI, 0.749–0.951). The PAS score could predict the length of ICU stay with sensitivity and specificity of 70.21% and 87.50, respectively (NPV, 33.3; PPV, 97.1; 95% CI, 0.605–0.906). Conclusions The standard FEES protocol using PAS score is a useful tool to assess aspiration in acute stroke patients and could be used to predict length of ICU stay and mortality.